Penerapan Senam Ergonomik terhadap Penurunan Tekanan Darah dan Asam Urat - Sri Muharni; Wulan Pramadhani; Umi Eliawati; Fanisa wahyuni (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2023)
Hypertension or high blood disease is actually a disorder of blood vessels that results in the supply of oxygen and nutrients carried by the blood is hampered to the body tissues in need.hypertension is often called the silent killer dark killer, because it includes diseases that women are declared hypertensive if their blood pressure is 160/95 mmHg. (Nurhaidar, 2010).In addition to hypertension, gout is now also a topic that is very much discussed by women, because most uric acid attacks women, especially the elderly. However, in this day and age it is not only the elderly who can get gout, adults can also get this gout. Irianto in his book entitled Public Health Science said that gout is referred to as a degenerative disease because the incidence rate is related to the degeneration process in old age that takes place according to time and age. (Simamora and Saragih 2019). Research conducted in the scientific journal Permas shows the results that of the 13 causes of gout, most of the causes are diet and lifestyle. So that those who should be more susceptible to gout are men because their serum uric acid levels are higher than women.(Sulistyoningtyas and Khusnul Dwihestie 2022).Community service activity entitled "Socialization on the Application of Ergonomic Gymnastics to Reduce Blood Pressure in Kabil Village, Kavling Baru, RT 003 RW 013, Danau Indah Punggur" The activity was welcomed by RW 013 Kavling Baru, Punggur with the hope of getting information about handling hypertension and gout, so as to control and prevent various kinds of disorders of the cardiovascular system in the form of hypertension, heart, or stroke that can interfere with public health.